A QSAR and Pharmacophore Survey on Tyrosine Kinase Inhibitors with Effect on Epidermal Growth Factor Receptor - Bozorgi, Atefeh Hajiagha; Samadi, Fatemeh (Current Enzyme Inhibition, 2024)
Backgroun Tyrosine kinases are of great importance nowadays in cancer treatment. As designing new inhibitors with more potency is an optimal goal of pharmaceutical companies, using previous improvements in this area would be beneficial. One of the most popular and widely used methods is creating a QSAR model. Another useful way is to build a pharmacophoric map to address important features of inhibitors. Methods Upon this, a large dataset of molecules was applied to create a QSAR model for the prediction of the inhibitory activity of molecules against the epidermal growth factor receptor. Using MOE software, molecular descriptors were calculated in 3d, and a model was built. Results 9 descriptors were selected, which describe the energy, shape, and hydrophobicity of the molecules. A pharmacophoric map was also created, and 3 important features were selected: Hydrophobic areas, H-bond acceptor regions, and Aromatic moieties. Conclusion These findings proved the results obtained result from the QSAR model.
Keywords: QSAR